THE APLIKASI HEEL RAISES EXERCISE DAPAT MENINGKATAN LENGKUNGAN KAKI DAN KESEIMBANGAN STATIS PADA ANAK-ANAK FLAT FOOT USIA 4-5 TAHUN DI TK AISYIYAH BUSTANUL ATHFAL 3 DENPASAR - Ariani, Liza; Wibawa, Ari; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia, 2015)
OBJECTIVE : To determine is there any increase on foot arch of the right foot, left foot and balace in children aged 4-5 years old with a flat foot after being given the heel raises exersice. SUBJECT : 26 healthy, were divided into two groups. Each group of 13 peoples. The first group get the heel raises exersice treatment and the second group without getting treatment. RESEARCH PLACE : Aisyiyah bustanul athfal 3 kindergarden, Denpasar. RESEARCH TIME : September – October 2014. MEASURING INSTRUMENT : Foot print and One legged stand test. RESEARCH DESIGN : This research used a experimental method, using two design group pre-test and post-test design. RESULTS : Each group were tested for normality by the Shapiro Wilk Test. First group showed the value of arch index p<0.05 it means data’s abnormally distributed and Second group showed the value of arch index p>0.05 it means data’s normally distributed. Although the value of the balance for First group and Second group showed p>0.05 it means data’s normally distributed. First group and Second group on different test with Mann Whitney U Test showing that both of the left foot’s arch index the groups get p value <0.05 and right foot’s the groups get p value p<0.05. The value of the balance showing that both of groups get p value <0.05, it means there is a significant difference between the heel raises exercise’s group (first group) and second group. In increasing the foot arch and balance. CONCLUSION : Based on the analysis of the research that has done, can be concluded that the application of heel raises exercise can increase the value of foot arch and balance. The application of heel raises exercise can give a significant difference for improving the value of foot arch and balance rather than without getting a treatment.
Keywords: heel raises exercise, foot arch, balance, arch index, one legged stand test